Can Real Exchange Rate Undervaluation Boost Exports and Growth in Developing Countries? Yes, But Not for Long - Haddad, Mona; Pancaro, Cosimo (World Bank, Washington, DC, 2012)
A policy of managed real undervaluation may have been an important factor behind the success of East Asia's export-led growth model. But current discussions over the value of China's currency demonstrate the controversy this kind of policy can generate. Although a managed real undervaluation can enhance domestic competitiveness, it is difficult to sustain both economically and politically in the post-crisis environment. The authors show that a real undervaluation works only for low-income countries, and only in the medium term.